Die «unerfüllt gebliebene Sehnsucht» der «Lebenskünstlerin» Lina Loos (Studia theodisca, 2015)
The role Lina Loos had to play in her artistic milieu involved a permanent struggle between her authentic self and the male-dominated society which obliged her to serve as an inspiring “muse”, first of all for her more famous husband Adolf Loos. This contrast was the object of her play Wie man wird, was man ist. This paper will attempt to outline Lina Loos’s struggle to stand as a woman writer in a society which rejected the female creative work, her social engagement during the Second World War and in the following years, as well as all the psychological contrasts and stylistic features characterising her literary and journalistic work.